2023
DOI: 10.5152/iao.2023.21387
|View full text |Cite
|
Sign up to set email alerts
|

Test-Retest Reliability, Effects of Age and Comparison of Horizontal 2 Semicircular Canals Gain Values between Head Impulse and Suppression Head Impulse Paradigms

Abstract: Background: This study investigates the test-retest reliability, aging effects, and differences in horizontal semicircular canals gain values between the head impulse paradigm and suppression head impulse paradigm. Methods: Sixty healthy adult subjects aged 22-76-year-old (mean ± standard deviation = 47.27 ± 18.29) participated in the head impulse paradigm and suppression head impulse paradigm using the video head impulse test. The Head impulse paradigm was used to asse… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 26 publications
0
1
0
Order By: Relevance
“…This phenomenon may stem from the limited sample size or the possibility of healthy children exhibiting immediate performance enhancements upon repeating the same task, a phenomenon commonly observed in psychometric assessments [27,28]. Previous research has also suggested that individual differences in motor development and learning capabilities may contribute to variations in test-retest reliability across different age groups [29]. However, further investigation is warranted to fully elucidate the underlying factors influencing the presence of outliers in correlation coefficients within specific age cohorts.…”
Section: Discussionmentioning
confidence: 99%
“…This phenomenon may stem from the limited sample size or the possibility of healthy children exhibiting immediate performance enhancements upon repeating the same task, a phenomenon commonly observed in psychometric assessments [27,28]. Previous research has also suggested that individual differences in motor development and learning capabilities may contribute to variations in test-retest reliability across different age groups [29]. However, further investigation is warranted to fully elucidate the underlying factors influencing the presence of outliers in correlation coefficients within specific age cohorts.…”
Section: Discussionmentioning
confidence: 99%